THE ARRIVAL OF CATHOLIC CHURCH IN THE ANGAMI AREA IN NAGALAND - *, KETHOLESIE (IJRDO-Journal of Applied Science, 2015)
This paper makes an attempt to trace some of the important events leading to the arrival of theCatholic Church in the Angami area and also the contribution of the Church to the overalldevelopment of the Angami Nagas.Christianity in Nagaland began with the arrival of the American Baptist missionariesin Upper Assam, extending their mission into the Hills. There are several Christiandenominations working in Nagaland such as the Catholics, the Baptists, the Christian RevivalChurch, the Assembly of God, the Pentecostal, the Seventh Day Adventist and the JehovahWitnesses.